β-Lactamases in Shigella flexneri Isolates from Hong Kong and Shanghai and a Novel OXA-1-Like β-Lactamase, OXA-30 - Siu, L. K. (American Society for Microbiology, 2000)
Ninety-one ampicillin-resistant Shigella flexneri strains from Hong Kong and Shanghai were studied for production of β-lactamases. TEM-1-like and OXA-1-like enzymes were identified in 21 and 79% of the strains, respectively, by isoelectric focusing (IEF). No difference in the pattern of β-lactamase production was found between strains from Hong Kong and Shanghai. Four ribotypes were detected. Over 88% of OXA-producing strains had the same ribotype. All TEM-1-like strains harbored a plasmid which hybridized positively with the bla(TEM) probe. Total DNA from OXA-1-like strains failed to hybridize or only hybridized weakly with an OXA probe. The OXA resistance was not transferable. OXA-1-like enzymes exhibited substrate and inhibition profiles similar to that of OXA-1 and were shown to have a pI of 7.3 by further IEF using a narrow-range ampholine gel. The gene encoding the OXA-1-like enzyme from one isolate (CH-07) was cloned, sequenced, and found to differ from bla(OXA-1) at codon 131 (AGA→GGA; Arg to Gly), resulting in the novel designation OXA-30. The predominance of OXA-type enzymes in ampicillin-resistant S. flexneri suggests host preference for specific β-lactamases.